Programa nacional de produção de biodiesel – PNPB. A cadeia de produção do biodiesel no estado de Tocantins: alavancadores e barreiras para o desenvolvimento regional e inclusão social - Furtado, Octaviano Sidnei (Universidade do Vale do Rio dos Sinos, 2016)
The need to produce energy to maintain the consumption levels of the productive systems has forced governments and society to seek new alternatives for generating energy. This has been done by associating economic factors like the reduction of oil by-product importation, reducing the emission of greenhouse gases and the social inclusion of family farmers aiming the regional development. These factors, among others, led Brazil to introduce the biodiesel in its national energetic matrix, launching the Biodiesel Production National Program (BPNP) in 2004. The addition of the biodiesel to the mineral diesel started being mandatory of 2% from 2008; nowadays, the compulsory addition is of 7% and starting on March 2019, the percentage will be 10%. This research aimed to analyze the leverage factors and the obstacles in the biodiesel productive chain in Tocantins, having as baseline the soybean as raw material. This work also investigates what is the PNPB contribution to the regional development and the social inclusion of the family farmers who provide it in the outskirts of the towns that make up the biodiesel production poles. The results demonstrate that the main leverage factors refer to the access to favorable financing conditions for farmers and processors, tributary exemption and production sales assurance. The foremost hindering elements are related to bureaucracy excess, gross earnings limits, lack of an associative organization or cooperative, in order to help the farmers. It is also observed the non - diversification of the raw material to biodiesel, what may be a potential risk factor. The study that was carried out suggests that a specific chain for the biodiesel was not planned nor created, but it was only subsumed to the already existing soybean production. Such action did not aggregated the family farmers to that chain and indicates the presence of mechanisms to obtain incentives, that the leverage of the program seems not to support itself with the current model of incentive to the insertion of the family farming, based on the soybean production as the main starting material. Thus, there is a demand of a governance structure implementation for the program in Tocantins.
Keywords: Biodiesel; Cadeia produtiva; Soja; Tocantins; Productive chain; Soybean; ACCNPQ::Engenharias::Engenharia de Produção